«The Human Clay»: David Hockney’s poetics (Itinera, 2021)
The contemporary artist David Hockney is well known as a painter of nature. However, what is the focus of his art? What is his self-appointed purpose as a painter? From a critical review of his numerous publications the answer arises naturally: humanity. David Hockney abandons abstraction and excessive naturalism, criticizes and uses photography (and other new medias) to find a way to better understand and express his humanity; to communicate his personal vision of the word. The subjects of his paintings – present or not – are humans and their peculiar way of looking, which is very different from that of a camera. Human vision takes place over time, and it carves the space. It is close to its object, and it is influenced by memory. Human beings are not only the subject but also the recipient of his work, he draws for humanity. He aims to educate himself on a more human perception and communicate it to others. Art education is visual education. Art sharpens the visual sense and makes it see the world as beautiful, thrilling and mysterious. Thus, by changing perception, it can change the world. If we look at the world more closely, if we allow ourselves to truly perceive the beauty of the ordinary, we can better love and care for our environment. This is Hockney’s duty as an artist, to paint humanity and its visual perception in order to make the world more human. In this overstimulating era of new media, he indicates to his anesthetized contemporaries a possible way to fight against their many distractions and emerging depressions and, perhaps, even to address major environmental issues.
Keywords: David Hockney, visual education, visual perception, aesthetics